Effect of novel double treatment on the properties of CdTe solar cells. (November 2021) - Kim, Sangsu; Song, Ju-Young; Kim, Deok; Hong, Jinki; Cho, Ick Joon; Kim, Yong Hyub; Jeong, Jae-Uk; Yoon, Mee Sun; Ahn, Sung-Ja; Chung, Woong-Ki; Nam, Taek-Keun; Cho, Shinhaeng
Abstract: In this study, the effect of Cl activation treatment on performance indicators of CdS/CdTe solar cells was investigated. We improved the performance of CdTe solar cells by applying a novel double treatment method that combines the CdCl2 dipping treatment and Freon (difluoro chloromethane) treatment methods that were previously studied. Conventional CdCl2 methanol dipping treatment (CdCl2 dipping treatment), Freon gas treatment that includes chlorine (Freon treatment), and CdCl2 dipping treatment + Freon treatment (double treatment) were performed, and the efficiencies, open circuit voltage (V OC ), and short circuit current (J SC ) for all three processes were observed. Although the efficiencies of the CdCl2 dipping treatment and Freon treatment were similar, there was a trade-off between the V OC and J SC in both processes. The double treatment sample shows an efficiency of 14.3%, which was higher than that of a single-treated sample. To investigate the characteristic change of each part of the solar cell, an equivalent circuit model in which the device was divided into a main junction and a back contact was used. In addition to electrical measurements, secondary ion mass spectroscopy (SIMS) and time of flight (TOF) analysis were performed. Through TOF measurement, drift mobility values for three treatment samples were calculated to be 1.1 cm 2 /Vs, 1.8 cm 2 /Vs, and 1.9 cm 2 /Vs, respectively. With TOF measurement, it was proved that the double treatment had a significant influence on the efficiency of the sample. Highlights: Equivalent circuit model of a CdTe-based solar cell was constructed. Back contact and main p–n junction changes for circuit model parts were measured. Methanol/CdCl2 dipping, Freon gas, and double treatments were conducted. Double treatment increases overall efficiency of solar cells. Main junction part of the solar cell maximally improved cell performance.